ANTICOLONIAL REVOLT IN XXI ST CENTURY BOLIVIA: THE CONTINUANCE OF “ INTERNAL CONFLICT” AND THE DEFEAT OF NEOLIBERAL PARTIES 2000-2003 - Choque Mendoza, Fredy (Revista de Historia Social y de las Mentalidades, 2024)
In order to explain the “changing process” that is nowadays experiencing Bolivia is necessary to go back to the origins of contemporary ethnic nationalism (post-52 period). In this socio-poli - tical rising process the whole of the indigenous movement has contributed, starting from diverse ideological positions and directing towards an horizon of self-determination in the beginning of the XXIst century. This process expresssed itself in the knowned as “Water Conflict” (2000) and finally in the “Gas Conflict” of 2003 by means of a general urban and rural indigenous uprise (to which the middle class mestizo adhered). An anticolonial and indianist revolt and a siege to colonial power upsurged that covers this period up to the fall of one of the most bloody neolibe - ral governments of the last decades. In this way a new period, characterized by the concealment of a president with aymara origins and a syndi - calist and socialist political standpoint (2005). Although other leftwing political sectors have contributed extensively to the Plurinacional state construction process, the Indianist and Katarist contribution is undeniable. In this article we enphasize likewise in the “decolonization pro - cess” and the construction of a true Plurinacional and Communitarian state.